The Use of Kurdification and Code-switching in SMS Texting by Kurdish Undergraduate Students at the University of Sulaimani - Sur, Shilan Ali Hama; Hameed, Othman Rashid (Sulaimani Journal for Humanities, 2025)
The advent of technology and social media resulted in an unprecedented ease in communication, especially the written form of communication, in ways that blurred the borders between nations and languages. This ease, however, is accompanied by certain technical limitations that resulted in changes in the structure of writing, punctuations and more importantly the language used for the communication. This research argues that code-switching is widespread among Kurdish students' SMS exchanges at the University of Sulaimani, and tries to find out whether this mixed-type of code together with the technical limitations results in a special types of language, or 'Kurdification', as it is the case in other languages, like Arabic. Samples of students’ SMS exchanges is collected over a period of 8 months from the students of the English Department, University of Sulaimani to measure the rate, frequency, and nature of code-switching in mobile text messaging, besides trying to indicate how both of the mobile property and the Roman script interact and result in producing Kurdification. The research found that codeswitching is used hand in hand with Kurdification and that codeswitching is bound to certain special sociolinguistic occasions. The research concluded that though the rate of Kurdification is higher than code-switching, however, it is not fully developed as an alternative way of writing.